Muhammad's Prophecy in Christianity and Islam: Debate and Controversy (Departement of Comparative Study of Religions, 2024)
The cross-religious debate that is most often discussed is about the claim of the apostle as the final Prophets, which is believed in Christianity that it never happened. The apostle was Muhammad Pbuh, an ordinary human being given advantages and privileges and elevated above all creatures. Contrary to the Christian belief that Isa or Jesus in the Christian belief is their greatest human being, the Bible is written about the arrival of a great figure that was promised. Therefore, this paper seeks to reveal the truth in Christian teachings regarding Muhammad as the complement of previous teachings. By including evidence from several figures from these two heavenly religions, namely Christianity and Islam, supported by evidence found in the Bible and al-Qur’an. The descriptive analysis method is used in this research to analyze the understanding of the two major religions of the world and related cross-religious teachings and doctrines. It’s supported by comparative methods that make it easier to see and know the comparisons found in both Islam and Christianity. A theological approach is used in this qualitative literature review, where the perspective of this writing is taken from studies that analyze scripts from holy books, discussing interfaith concepts and matters related to doctrine in religion. With this research it is hoped that further researchers will be able to take the value if necessary to be refined with an explanation broader and complete the deficiencies contained in this writing.